2013
DOI: 10.1155/2013/354276
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Training in Patients Recovering Recent Open Cardiothoracic Surgery: A Randomized-Controlled Trial

Abstract: Objectives. To evaluate the clinical efficacy and feasibility of an expiratory muscle training (EMT) device (Respilift) applied to patients recovering from recent open cardiothoracic surgery (CTS). Design. Prospective, double-blind, 14-day randomised-controlled trial. Participants and Setting. A total of 60 inpatients recovering from recent CTS and early admitted to a pulmonary rehabilitation program. Interventions. Chest physiotherapy plus EMT with a resistive load of 30 cm H2O for active group and chest phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This finding was in agreement with by Crisafulli et.al, (2013) (60) and Valkenet et.al, (2013) (61) who found that the majority of studied groups had coronary artery bypass graft surgery and valve surgery. Also, Kodric et.al, (2013) (56) reported that the majority of the studied groups underwent coronary artery bypass graft surgery.…”
Section: Effect Of Inspiratory Muscle Training On Clinical Outcomes Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was in agreement with by Crisafulli et.al, (2013) (60) and Valkenet et.al, (2013) (61) who found that the majority of studied groups had coronary artery bypass graft surgery and valve surgery. Also, Kodric et.al, (2013) (56) reported that the majority of the studied groups underwent coronary artery bypass graft surgery.…”
Section: Effect Of Inspiratory Muscle Training On Clinical Outcomes Ofsupporting
confidence: 93%
“…Moreover, the findings of the current study were supported by Kodric et.al, (2013) (56) whoconcluded that training of inspiratory muscles has a positive effect on dyspnea and activities of daily living. Crisafulli et.al, (2013) (60) observed that dyspnea improved faster and more significantly in the study when compared with control group. In contrast, Jeong et.al, (2015) (75) found that dyspnea was reduced in the study group but this reduction was not statistically significant.…”
Section: Effect Of Inspiratory Muscle Training On Clinical Outcomes Ofmentioning
confidence: 66%
“…In an evaluation of the clinical efficacy and feasibility of a respiratory muscular training device applied to patients after cardiothoracic surgery, Crisafulli et al. (24) observed improvement in both IP max and EP max 14 days after surgical procedures associated with the use of the device. While IP max refers mainly to the force of the diaphragm, EP max mainly reflects the strength of the abdominal and intercostal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in lung volumes and capacities contributes to changes in gas exchange, resulting in hypoxemia and decreased diffusion capacity [13] [14]. Atelectasis, pleural effusion, and pneumonia are pulmonary complications frequently found [12] [16] [17]. However, other complications such as hypercapnia, reintubation, and respiratory failure are also observed [14].…”
Section: Introductionmentioning
confidence: 99%